2005
DOI: 10.1021/la0479105
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatics of PEGylated Micelles and Liposomes Containing Charged and Neutral Lipopolymers

Abstract: The electrostatics of large unilamellar vesicles (LUVs) of various lipid compositions were determined and correlated with steric stabilization. The compositional variables studied include (a) degree of saturation, comparing the unsaturated egg phosphatidylcholine (EPC) and the fully hydrogenated soy phosphatidylcholine (HSPC) as liposome-forming lipids; (b) the effect of 40 mol % cholesterol; (c) the effect of mole % of three methyl poly(ethylene glycol) (mPEG)-lipids (the negatively charged mPEG-distearoyl ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 40 publications
5
39
0
3
Order By: Relevance
“…The finding that the zeta potential of lipid assemblies containing PEG-DSPE is negative is in agreement with our previously reported data (31). It also supports the "hidden charge effect" that was suggested for liposomes sterically stabilized through grafting of mPEG-DSPE with PEG moiety ≥0.75 kDa (34,35). Similar to their conventional counterpart, these liposomes can be considered "neutral."…”
Section: Resultssupporting
confidence: 91%
“…The finding that the zeta potential of lipid assemblies containing PEG-DSPE is negative is in agreement with our previously reported data (31). It also supports the "hidden charge effect" that was suggested for liposomes sterically stabilized through grafting of mPEG-DSPE with PEG moiety ≥0.75 kDa (34,35). Similar to their conventional counterpart, these liposomes can be considered "neutral."…”
Section: Resultssupporting
confidence: 91%
“…Comparison of the effective electrophoretic mobilities (m ep = m tot 2 m eo ) of atenolol with the different coatings and carriers showed that there were no strong interactions of the positively charged analyte with the PEG-lipid membranes under these conditions (HEPES, pH 7.4). A recent study of the interaction between spermine (cationic, molar mass about 200 g/mol) and DSPEG2000-containing liposomes by fluorescence spectroscopy, showed low (or no) affinity of spermine to the liposome surface [30]. Our results agree with this.…”
Section: Separation Of Low-molar-mass Analytessupporting
confidence: 91%
“…The higher the molar mass of PEG (i.e., the longer the PEG chain), the lower was the surface charge of the vesicles. This can be explained in terms of shielding of the negatively charged vesicle surface by the exposed PEG chains, which decreased the zeta potential of the vesicle [29,30]. However, the zeta potential of the POPC/DMPEG3000 aggregates was about 213 mV, which shows that the shorter C14 chains of the DMPEG-lipid clearly affect the packing of the lipids in the liposome.…”
Section: Zeta Potentials Of the Pegylated Aggregatesmentioning
confidence: 99%
“…An aliquot of 100 L of liposomes or lipoplexes was diluted in 600 L of 20 mM Hepes (pH 7.4). The principle of zeta potential measurement and equation for calculation are described elsewhere [37].…”
Section: Preparation and Characterization Of Sirna Cationic Liposome mentioning
confidence: 99%